Epidemiological status and associated factors of frailty and pre-frailty in older adults with asthma in China: A national cross-sectional study - Zeng, Xue-zhai; Meng, Ling-bing; Jia, Na; Shi, Jing; Zhang, Chi; Li, Ying-ying; Hu, Xing; Hu, Jia-bin; Li, Jian-yi; Wu, Di-shan; Li, Hui; Qi, Xin; et al. (Frontiers in Public Health, 2023)
Objective There are few studies on the prevalence and factors associated with frailty and pre-frailty in older adults with asthma worldwide. The aim of this study was to examine the epidemiological status and factors associated with frailty and pre-frailty in older adults with asthma in China. Research design and methods Data were obtained from the Sample Survey of Aged Population in Urban and Rural China in 2015, a nationwide cross-sectional survey covering 224,142 older people aged 60 years or older in 31 provinces/autonomous regions/municipalities in mainland China. We performed frailty and pre-frailty assessments using the frailty index, and the diagnosis of asthma in the older adults was self-reported based on the history of the physician's diagnosis. Results Nine thousand four hundred sixteen older adults with asthma were included in the study. The age-sex standardized prevalence of frailty and pre-frailty in Chinese older adults with asthma was 35.8% (95% CI 34.8%−36.7%) and 54.5% (95% CI 53.5%−55.5%). Multinomial logistic regression analysis showed that increased age, female, illiteracy, living alone, poor economic status, ADL disability, comorbid chronic diseases, previous hospitalization in the past year, and residence in northern China were associated with frailty and pre-frailty in older adults with asthma. Conclusion The prevalence of frailty and pre-frailty in Chinese older adults with asthma is very high, and assessment of frailty should become routine in the management of older adults with asthma. Appropriate public health prevention strategies based on identified risk factors for frailty in older adults with asthma should be developed to reduce the burden of frailty in Chinese older adults with asthma.